CO2 fluxes and biomass during experimental herbivore exclusion and shrub introduction - Sørensen, Mia Vedel; Graae, Bente Jessen; Hagen, Dagmar; Enquist, Brian Joseph; Nystuen, Kristin Odden; Strimbeck, Richard (Dryad Digital Repository, 2018)
Field data of CO2 fluxes (including Net Ecosystem Exchange, Ecosystem Respiration and Gross Ecosystem Photosynthesis) and the environment (such as light, moisture, and air, surface, and soil temperature) during measurements and vegetation data (including absolute abundance and measured and estimated biomass of functional groups). Methods and experimental design is explained in publication. The data is processed in R core Team 2017.